2023
DOI: 10.1183/16000617.0144-2022
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting interleukin-33 and thymic stromal lymphopoietin pathways for novel pulmonary therapeutics in asthma and COPD

Abstract: Interleukin-33 (IL-33) and thymic stromal lymphopoietin (TSLP) are alarmins that are released upon airway epithelial injury from insults such as viruses and cigarette smoke, and play critical roles in the activation of immune cell populations such as mast cells, eosinophils and group 2 innate lymphoid cells. Both cytokines were previously understood to primarily drive type 2 (T2) inflammation, but there is emerging evidence for a role for these alarmins to additionally mediate non-T2 inflammation, with recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 134 publications
0
8
0
Order By: Relevance
“…[69][70][71] However, over the past decade, a new wave of biologics targeting the cytokines IL-4, IL-13, IL-5, IL-33, thymic stromal lymphopoietin (TSLP), IL-31 and/or their receptors have heralded a new age in the treatment of diseases including asthma, atopic dermatitis, chronic rhinosinusitis with nasal polyps, eosinophilic esophagitis and other diseases. 6,72,73 In line with the efficacy of several new biologics, we have come to a greater appreciation of endotypes of allergy, which greatly inform patient treatment options. Patients are no longer stratified only on the basis of IgE, but on the expression type 2 cytokines, levels of eosinophils, presence of airway inflammation (fractional exhaled nitric oxide) and on specific allergen reactivities.…”
Section: What Are the Most Interesting Advances In Allergy Research O...mentioning
confidence: 99%
See 1 more Smart Citation
“…[69][70][71] However, over the past decade, a new wave of biologics targeting the cytokines IL-4, IL-13, IL-5, IL-33, thymic stromal lymphopoietin (TSLP), IL-31 and/or their receptors have heralded a new age in the treatment of diseases including asthma, atopic dermatitis, chronic rhinosinusitis with nasal polyps, eosinophilic esophagitis and other diseases. 6,72,73 In line with the efficacy of several new biologics, we have come to a greater appreciation of endotypes of allergy, which greatly inform patient treatment options. Patients are no longer stratified only on the basis of IgE, but on the expression type 2 cytokines, levels of eosinophils, presence of airway inflammation (fractional exhaled nitric oxide) and on specific allergen reactivities.…”
Section: What Are the Most Interesting Advances In Allergy Research O...mentioning
confidence: 99%
“…Omalizumab (a monoclonal targeting IgE) was first approved for use in 2003 and demonstrated efficacy in moderate–severe asthmatics 69–71 . However, over the past decade, a new wave of biologics targeting the cytokines IL‐4, IL‐13, IL‐5, IL‐33, thymic stromal lymphopoietin (TSLP), IL‐31 and/or their receptors have heralded a new age in the treatment of diseases including asthma, atopic dermatitis, chronic rhinosinusitis with nasal polyps, eosinophilic esophagitis and other diseases 6,72,73 . In line with the efficacy of several new biologics, we have come to a greater appreciation of endotypes of allergy, which greatly inform patient treatment options.…”
Section: What Are the Most Interesting Advances In Allergy Research O...mentioning
confidence: 99%
“…31 The molecular pathways that can be targeted include T2 cytokines, IgE, thymic stromal lymphopoietin (TSLP), and IL-33 etc. [32][33][34] The latest research shows that ferroptosis may be an emerging target in inflammatory diseases. 10 Authors identified that ferroptosis inhibitor alleviates bronchial epithelial cell injury in asthma.…”
Section: Ferroptosis Triggers Airway Inflammation In Asthmamentioning
confidence: 99%
“…It is found in multiple organs and is mainly localized to barrier epithelial cells and endothelial cells. Fibroblasts, myo broblasts, and airway smooth muscle cells were also found to express Il-33 [19,20]. (Byers et al, 2013Calderon et al, 2023.…”
Section: Introductionmentioning
confidence: 96%
“…Fibroblasts, myo broblasts, and airway smooth muscle cells were also found to express Il-33 [19,20]. (Byers et al, 2013Calderon et al, 2023.…”
Section: Introductionmentioning
confidence: 96%